Web-based solution for acquisition, processing, archiving and diffusion of endoscopy studies - Laranjo, Isabel (2013)
In this paper we present a distributed solution for the acquisition, processing, ar- chiving and diffusion of endoscopic procedures. The goal is to provide a system capable of managing all administrative and clinical information (including audiovisual content) since the acquisition process to the searching process of previous exams, for comparison with new cases. In this context, a device for the acquisition of the endoscopic video was de- signed (MIVbox), regardless of the endoscopic camera that is used. All the information is stored in a structured and standardized way, allowing its reuse and sharing. To facilitate this sharing process, the video undergoes several processing steps in order to obtain a summa- rized video and the respective content characteristics. The proposed solution uses an anno- tation system that enables content querying, thus becoming a versatile tool for research in this area. A streaming module in which the endoscopic video is transmitted in real time is also provided.